Arteriohepatic Dysplasia (Alagille Syndrome) in a Child (Clinical Case) - Ye.V. Omelchenko; A.S. Senatorova; A.F. Shipko; A.V. Omelchenko-Seliukova; M.N. Yermolaiev; M.M. Yermolaieva; Yu.A. Levchenko (Zaslavsky O.Yu., 2015)
The article presents a clinical case of a child with a rare nosology - Alagille syndrome. Among the causes of neonatal cholestasis, Alagille syndrome is ranked second, it occurs with an incidence of 1 per 70,000 of newborns. This syndrome is characterized by an insufficient number or by a small diameter of intrahepatic bile ducts, which carry bile from the liver. Alagille syndrome includes a combination of at least three of the five main symptoms: chronic cholestasis, cardiovascular defects, abnormalities of the spine, eye defects, typical craniofacial signs. The only definitive therapy with the formation of liver cirrhosis and without gross defects is liver transplantation.